ENGARUH BIAYA KEAGENAN, TAHAP DAUR HIDUP PERUSAHAAN, KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN UTANG SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Muhammad Yasfi; Kurniawan Ali Fachrudin (Universitas Ahmad Dahlan, 2014)
One of the company's main objective was to enhance firm value through increased prosperity of the owners or shareholders. The separation of ownership from management in corporation creates agency problem. Managers who run companies and usually do not have stock ownership may not act in the shareholder’s best interest because they maximize their own wealth.The objective of this research was to examine whether there was an effect of agency cost (dispersion of ownership and managerial ownership), firm life cycle stages, and dividend policy on firm value with debt policy as moderating variable. The population of the study is the manufacturing companies that registered in Indonesian Stock Exchange in the period of 2002–2012. Samples of 88 observations are selected using purposive sampling method. The analysis method of this research was simple regression and Moderated Regression Analysis (MRA).The result showed that dispersion of ownership and firm life cycle stages can influence firm value. The result also showed that debt policy can moderating dispersion of ownership influence firm value.